Speech-Language Therapy Given to King George VI in The King's Speech Movie (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
Language is a vital ability that one person should have in order to get connected with other people. One of the possible ways to build a good relationship with other people is speech, which cannot be separated from language. Unfortunately, not all people have the ability to manage their speech. Such problem called by psycholinguists as speech disorder is well captured in a true story movie entitled The King's Speech. The main character in the movie, King George VI, has some difficulties to produce language especially when he has to perform speech in public. This research aimed to figure out the phenomena of speech disorder found in the movie. Using descriptive qualitative approach, the writer attempted to analyze the language productivity problems and the possible therapy given to solve the problems. The results show that King George VI has several speech disorder such as disfluency, articulation disorder and muteness. But, with some treatments, such as, muscle strengthening exercises, breathing strengthening exercises and phonetics therapy, he finally could reduce and overcome his speech disorder much better than the one he had beforehand.